Dukungan Keluarga terhadap Manajemen Hipertensi pada Lansia di Indonesia - Annisa, Nadiya Sahara; Haryanto, Joni; Kristiawati, Kristiawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the impact of family support on the management of hypertension in the elderly. The method used is PRISMA as a guide in choosing articles. Search articles using Medical Subject Heading (MeSH) with keywords Family Support or Family Engagement AND Management or Controlling and Hypertension or High Blood Pressure AND Elderly. The article used cross-sectional, quasi-experimental and descriptive studies published from 2018-2023 that discussed the relationship of family support with hypertension control in the elderly. The assessment is based on the Joanna Briggs Institute's (JBI) Critical Appraisal. The results showed that a total of 9 articles that fit the inclusion criteria were analyzed in this study. Participants in the study were families and elderly people with hypertension. All related studies on the effectiveness of providing family support for the management of hypertension in the elderly such as increased family roles, increased adherence to taking medication in the elderly, providing regular physical activity, facilitating the elderly to go to health facilities, prioritizing elderly worship activities, allowing the elderly to choose activities they like while still paying attention to health behavior to improve the quality of life for the elderly with hypertension. Conclusion, families are expected to always support the elderly in order to improve the management of hypertension. Keywords: Elderly, Family Support, Hypertension Management